Evaluation of a biosensor based on reduced graphene oxide and glucose oxidase enzyme on the monitoring of second-generation ethanol production - Donini, Caruane A. [UNESP] (2020)
An easily prepared biosensor based on reduced graphene oxide (rGO) and glucose oxidase (GOx) enzyme was developed to monitor the enzymatic hydrolysis process of the second-generation (2G) ethanol process from green coconut biomass. The rGO-GOx biocomposite that modified a glassy carbon (GC) electrode was characterized by morphological, electrochemical and spectrophotometric techniques showing that the GOx enzyme was immobilized on the rGO. The parameters for glucose determination were optimized by square wave voltammetry (SWV). The developed biosensor was applied for the determination of glucose during the enzymatic hydrolysis step, showing that the process can be stopped with 12 h of reaction. Thus, an important achievement of this analysis is the reduced time to get a valuable result for the test, saving time and reducing the cost of the 2G ethanol process.